Deficiency of the interleukin-1 receptor antagonist: Characterizing the molecular consequences of loss-of-function IL1RN variants from structural and biochemical evidence - Joshua Pillai; Spencer Fang (Clinical Immunology Communications)
Deficiency of interleukin-1 receptor antagonist (DIRA) is a rare autoinflammatory disease with neonatal onset defined by periostitis, pustulosis, and sterile osteomyelitis. DIRA is caused by biallelic loss-of-function mutations in the IL1RN gene, including 16 cytogenetic abnormalities to date. Due to the rarity of the condition, limited studies have evaluated the molecular basis and consequences of pathogenic IL1RN variants. Herein, we reviewed structural data from the crystal structure of IL-1Ra/IL-1R1 complex along with complementary experimental evidence from prior studies to characterize impacts on protein folding and binding affinity to IL-1R1. Furthermore, we define the hypomorphic R26X variant and suggest that genomic distance influences the ability of translation reinitiation in the context of DIRA, as another variant in the N-terminal did not undergo the same mechanism. Lastly, we provide a multiple-sequence alignment and structural template to better streamline analyses and reporting of novel IL1RN variants in the near future.